STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PADA UMKM TAKOTO JOMBANG - Adena Khumairoh; Novita Nur Fitria Dewi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Competition in the business world is increasingly diverse, encouraging companies to compete in competing markets and consumers. This is what happened to the Takoto UMKM. This study aims to determine the marketing strategies used by UMKM Takoto to increase sales. This type of research is conducted using descriptive qualitative methods in the form of case studies on the Takoto UMKM business. This study aims: (1) to study the marketing strategy (marketing mix) of products at UMKM Takoto. (2) provide alternative marketing suggestions for UMKM Takoto products. The conclusions of this study are: (1) the product is considered good by consumers and already has 5 elements of product strategy such as product attributes, brand, packaging, and labels, but the product does not last long because it uses ingredients that do not contain preservatives; (2) the pricing strategy is oriented towards production costs so that in the future it can be considered for pricing by looking at the prices of competitors' products; (3) the promotion strategy of Takoto's UMKM pastries is still limited because it uses more personal selling rather than intense promotion through advertising; (4) Takoto's UMKM pastry products are marketed directly to consumers and through retailers, however the dominant marketing is direct to consumers so that the bargaining position is stronger because it does not depend on retailers.